Content Analysis of Library’s Facebook Confession Page “Kao-Bei Library” - Jia-En Lee; Hao-Ren Ke (Jiàoyù zīliào yǔ túshūguǎn xué, 2020)
The popularity of social media has changed how people communicate with each other and know about the world. Some social media provide the anonymous feature to increase the willingness of users to express their opinions, and confessions pages on Facebook are one kind of them. Confessions pages on Facebook are both popular and controversial. This study analyzes 1,080 posts on the Facebook confessions page “Kao-Bei Library” to explore user activities and post features. This study developed a coding scheme which includes the identities of posters, the purposes of posts, objects of complaints, and the identifies of librarians who were complained by other librarians. The result indicates that the frequency of posts has no differences between week days. The timing of posts bears a resemblance to people’s daily routine. Most posters do not reveal their identities, while the most identified are librarians. Posts on the page are mainly complaints, followed by posts responding to previous posts. Each poster from different backgrounds has a unique trait in their words. The result can apply to organizational management, expecting anonymous social media to be considered as a tool to understand the relationships within an organization, thus pay more attention to the potential crisis. Also, this study provides suggestions for anonymous social media studies and librarian’s human resource studies.